Comparative Study on Haematological and some Biochemical Parameters of Rabbit, Oryctolagus cuniculus and Partridge, Francolinus francolinus from Iraqi Environment - Amer , Nusaibah; Dauod, Hussain A.M. (Iraqi Journal of Science, 2022)
The present study aimed to establish reference normal ranges of haematological and biochemical parameters of two vertebrates (rabbits and partridges). Twenty animals (10 rabbits, 10 partridges) were used in this study. Blood samples, collected from heart of rabbits, as well from the right jugular vein of partridge, and delivered to the laboratory. Some biochemical parameters (potassium, sodium, and uric acid) have been investigated, in addition blood samples were tested for: white blood cells (WBC), red blood cells (RBC), haemoglobin (HB), haematocrit (HCT), mean corpuscular hemoglobin (MCH), mean concentration of hemoglobin in the corpuscular volume (MCHC), mean corpuscular volume (MCV).Results indicate that haematological and biochemical data are revealed statistically significant differences between rabbit and partridge in most parameter except sodium and potassium were showed no significantly different. The RBC and MCHC levels were significantly higher (P<0.05) in rabbit than in partridge. While, the results showed higher significant (P<0.05) in HB, HCT, MCV, and MCH concentrations were observed in partridge than in rabbit. White blood cells (lymphocytes, monocytes, and granulocytes) showed significant increase in partridge than in rabbit. Some biochemical values are showed non-significant difference in potassium and sodium value between rabbits and partridge. While, the uric acid showed significantly increase (P<0.05) in partridge than in rabbit.